Drawing-based Story Telling Influence on Children Language Development and Social Aspect - Hariddha Yuni Sulistyaningrum; Imanuel Hitipeuw; Triyono Triyono (Pascasarjana UM, 2018)
Abstract: Language and social development of children plays an important role in influencing further development. The objectives of this research are to determine the effect of drawing based on story-telling toward language development and social development of children age 5–6 years. Single subject research with reversal design ABAB was used in this experimental research. Four kindergarten children identified having language and social problems became the subjects. The observation was used to collect data. In addition, the data were put into graphs to be analyzed by using visual inspection. The results showed that drawing activities based on story telling could improve the scores of language development for each subject; and also improves the pro-social attitude of each subject. And at the same time the aggressive attitude for each subject decreased. It concludes that drawing based on story telling improve language and social development of children aged 5–6 years effectively.Key Words: drawing, story telling, language, socialAbstrak: Perkembangan bahasa dan sosial anak berperan penting dalam mempengaruhi perkembangan selanjutnya. Tujuan penelitian ini adalah untuk mengetahui pengaruh menggambar berbasis story telling terhadap perkembangan sosial anak usia 5–6 tahun. Single subject research dengan reversal design digunakan dalam penelitian. Subjek penelitian adalah empat siswa kelas B TK yang diketahui memiliki masalah bahasa dan sosial. Instrumen pengumpulan data adalah observasi. Analisis data dengan pemeriksaan visual terhadap data yang ditampilkan oleh grafik. Hasil penelitian menunjukkan menggambar berbasis story telling mampu meningkatkan skor perkembangan berbahasa masing-masing subjek; dan mampu meningkatkan sikap pro sosial untuk masing-masing subjek, di sisi lain sikap agresif untuk masing-masing subjek ikut menurun. Simpulan penelitian bahwa menggambar berbasis story telling efektif meningkatkan perkembangan berbahasa dan sosial anak usia 5–6 tahun.Kata kunci: menggambar, story telling, bahasa, sosial